Luisa Fernanda [zarzuela in three acts] - Sagi, Emilio; Ramírez, Angel Luis; Herrera, Nancy Fabiola ca. 20./21. Jh; Cantarero, Mariola 1978-; Bros, José 1960-; Domingo, Plácido 1941-; Pierotti, Raquel 1952-; López Cobos, Jesús 1940-2018 (Opus Arte, 2007)
"This production, made by Emilio Sagi for the Teatro Real, Madrid, was based on his earlier staging for a concert performance of Luisa Fernanda at La Scala, Milan and was recorded live at the Teatro Real, Madrid"--Container.
Interpr. u.a.: Nancy Herrera (Luisa Fernanda). Mariola Cantarero (Duchess Carolina). José Bros (Javier Moreno). Placido Domingo (Vidal Hernando). Raquel Pierotti (Mariana). Chorus and Orchestra of the Teatro Real (Madrid Symphony Orchestra and Chorus). Jesús López Cobos (Dir.). Emilio Sagi (Bühnenregie). Ángel Luis Ramírez (Filmregie). - Live-Aufn.: Madrid, Teatro Real, 14. und 16. Juli 2006. - Enth. Bonus-Material
Keywords: Operas; DVD-Video